Bad dream, nightmares and psychopathology: a systematic review - Faccini, Julie; Del-Monte, Jonathan (Frontiers in Psychiatry, 2024)
Objective: Bad dreams and nightmares can have a strong psychological impact. However, although the scientific literature points in the direction of an established association between nightmares and psychopathology, many of the studies investigating these links have been carried out on a general population. This systematic literature review aimed to identify studies that have used a sample from a population with a diagnosis of psychopathological disorders or a diagnosis of nightmare disorder, to highlight the state of knowledge concerning the link between bad dreams, nightmares, and psychopathology. Method: The systematic review included all cross-sectional and longitudinal studies conducted on a psychiatric population in which variables related to bad dreams and/or nightmares were examined and published since 2014. The search was conducted in May 2024 in the PsychINFO and PubMed databases.Results: A total of 34 studies published over the last decade met the inclusion criteria.Conclusions: Psychiatric populations are significantly more affected by nightmares and bad dreams than the general population. Furthermore, the presence of nightmares tends to maximize the clinical symptomatology of patients. However, there are still too few studies available to understand the basis of this relationship.